CAXII inhibitors: Potential sensitizers for immune checkpoint inhibitors in HCC treatment - Rui Han; Rui Han; Rui Han; Rui Han; Rui Han; Jiayin Li; Jing Hony; Jing Hony; Zhiwei Xiao; Jinghui wang; Man Yao; Man Yao; et al. (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is a lethal malignancy with a lack of effective treatments particularly for the disease at an advanced stage. Even though immune checkpoint inhibitors (ICIs) have made great progress in the treatment of HCC, durable and ideal clinical benefits still cannot be achieved in plenty of patients with HCC. Therefore, novel and refined ICI-based combination therapies are still needed to enhance the therapeutic effect. The latest study has reported that the carbonic anhydrase XII inhibitor (CAXIIi), a novel type of anticancer drug, can modify the tumor immunosuppression microenvironment by affecting hypoxic/acidic metabolism and alter the functions of monocytes and macrophages by regulating the expression of C-C motif chemokine ligand 8 (CCL8). These observations shine a light on improving programmed cell death protein 1 (PD-1)/programmed cell death ligand-1 (PD-L1) immunotherapy in combination with CAXIIis. This mini-review aims to ignite enthusiasm to explore the potential application of CAXIIis in combination with immunotherapy for HCC.